Analytical procedures for the determination of selected trace elements in peat and plant samples by inductively coupled plasma mass spectrometry - Krachler, Michael; Mohl, Carola; Emons, Hendrik; Shotyk, William (Spectrochimica acta. Part B, Atomic spectroscopy, 2002)
A simple, robust and reliable analytical procedure for the determination of 15 elements, namely Ca, V, Cr, Mn, Co, Ni, Cu, Zn, Rb, Ag, Cd, Ba, Tl, Th and U in peat and plant materials by inductively coupled plasma-quadrupole mass spectrometry (ICP-QMS) was developed. Powdered sample aliquots of approximately 220 mg were dissolved with various acid mixtures in a microwave heated high-pressure autoclave capable to digest 40 samples simultaneously. The selection of appropriate amounts of digestion acids (nitric acid, hydrofluoric acid or tetrafluoroboric acid) was crucial to obtain accurate results. The optimized acid mixture for digestion of plant and peat samples consisted of 3 ml HNO3 and 0.1 ml HBF4. An ultrasonic nebulizer with an additional membrane desolvation unit was found beneficial for the determination of Co, Ni, Ag, Tl, Th and U, allowing to aspirate a dry sample aerosol into the ICP-QMS. A pneumatic cross flow nebulizer served as sample introduction device for the other elements. Internal standardization was achieved with 103Rh for all elements, except for Th whose ICP-QMS signals were corrected by 103Rh and 185Re. Quality control was ascertained by analysis of the certified plant reference material GBW 07602 Bush Branches and Leaves. In almost all cases HNO3 alone could not fully liberate the analytes of interest from the peat or plant matrix, probably because of the silicates present. After adding small amounts (0.05-0.1 ml) of either HF or HBF4 to the digestion mixture, concentrations quantified by ICP-QMS generally increased significantly, in the case of Rb up to 80%. Further increasing the volumes of HF or HBF4 in turn, resulted in a loss of recoveries of almost all elements, some of which amounted to approximately 60%. The successful analytical procedures were applied to the determination of two bulk peat materials. In general, good agreement between the found concentrations and results from an inter-laboratory trial or from instrumental neutron activation data were obtained, underpinning the suitability of the developed analytical approach.
Gesehen am 06.10.2020